2006
DOI: 10.1071/ap06027
|View full text |Cite
|
Sign up to set email alerts
|

Peronospora lamiion Lamiaceae in Australia

Abstract: Abstract.A detailed description and illustration of the Australian specimens of Peronospora lamii on Salvia spp. and on Lamium amplexicaule (Lamiaceae) are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…on S . officinalis in 1993 (McMillan, 1993), the disease has been reported from all over the world (Gamliel and Yarden, 1998; Hill et al , 2004; Belbahri et al , 2005; Liberato et al , 2006; Humphreys‐Jones et al , 2008). It is of increasing economical concern and can be regarded as a newly emerging disease.…”
Section: Introductionmentioning
confidence: 99%
“…on S . officinalis in 1993 (McMillan, 1993), the disease has been reported from all over the world (Gamliel and Yarden, 1998; Hill et al , 2004; Belbahri et al , 2005; Liberato et al , 2006; Humphreys‐Jones et al , 2008). It is of increasing economical concern and can be regarded as a newly emerging disease.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier reports of downy mildews on sage species mention the occurrence of P. lamii and P. swinglei on S. pratensis (meadow sage), S. lanceolata (lance-leaf sage) or S. sclarea (clary sage) but not on S. officinalis (Rabenhorst 1857;Ellis and Kellerman 1887;Gäumann 1923;Kochman 1970;USDA 1960;Osipjan 1967;Stanjavičenie 1984). In the meantime, downy mildew on common sage has been reported from Israel, Austria, Italy, New Zeeland, Australia, UK and Germany (Gamliel and Yarden 1998;Plenk 2002;Hill et al 2004;Belbahri et al 2005;Liberato et al 2006;Humphreys-Jones et al 2008;Choi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is also still unclear how the disease was able to spread throughout the world so quickly. It was hypothesized that downy mildew on S. officinalis might has been distributed by contaminated seed lots (Choi et al 2009), but proof for this hypothesis is still lacking and oospores, which could play an important role in the spread of the disease, have been reported only on sage leaves (Plenk 2002;Liberato et al 2006;Humphreys-Jones et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Our investigations have revealed that P. musarum which causes freckle disease induces several defences in the peel which restrict development of anthracnose disease by C. musae. The freckle of leaf and fruit of bananas and plantains has been recorded in the Asia, Pacific, Americas, and more recently in Australasia-Oceania and South and South East Asia ( Liberato et al, 2006 ). The disease is characterized by minute, isolated pin-head sized spots in the superficial cell layers of the banana fruit peel.…”
mentioning
confidence: 99%